Construction of models of analysis and forecasting of the level of risks of the banking sector of the Republic of Belarus on the basis of integrated indicators - Suvalau, Valentin O.; Miniukovich, Katsiaryna A. (Journal of the Belarusian State University. Economics, 2018)
The process of constructing an econometric model for the purposes of creating an automated algorithm for forecasting the level of risks in the banking sector of the Republic of Belarus is being explored. The internal properties of the algorithm are based on the formalization of the process of constructing an econometric model with the fulfillment of the prerequisites, as well as machine learning.
Keywords: model; forecasting; risks; econometric tools; integrated indicators; banking sector